2010
DOI: 10.1089/jpm.2009.0259
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden in HIV-Infected Adults at Time of HIV Diagnosis in Rural Uganda

Abstract: This study demonstrates that the burden of HIV-related symptoms in individuals presenting for care in Uganda is significant and debilitating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 34 publications
(34 reference statements)
4
49
4
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17]37 It is clear from prior data that pain is a considerable burden on HIV-positive, cancer, and end-stage patients. This study now establishes that hospitalized patients also carry a significant amount of pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17]37 It is clear from prior data that pain is a considerable burden on HIV-positive, cancer, and end-stage patients. This study now establishes that hospitalized patients also carry a significant amount of pain.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Beyond actively dying patients and those with fatal malignancies, patients with chronic conditions also experience untreated pain-studies have found the prevalence of pain to be 59% to 98% among HIV/AIDS patients in South Africa, Uganda, and Kenya. [14][15][16][17] Research on the correlates of pain in SSA has found that in HIV patients, pain has been associated with increasing age, female gender, not being on antiretroviral therapy, number of symptoms, advanced disease, number of medical comorbidities, and reduced functional performance scores. [18][19][20] These studies are specific to ambulatory HIV/AIDS patients, and to date no research has been conducted to determine the burden of pain in a mixed inpatient hospital setting in SSA.…”
mentioning
confidence: 99%
“…While instruments like the Memorial Symptom Assessment Scale have been used to assess symptoms in patients with heart failure (68-70), COPD (71,72), and HIV disease (11,73), the most valid and reliable instrument to assess symptoms for symptom cluster research across a variety of chronic conditions is yet to be developed.…”
Section: Transferability To Other Chronic Conditionsmentioning
confidence: 99%
“…9,47 The MSAS-SF has been widely used in describing symptom experience in HIV/AIDS patients and in African settings. 63,66 Each physical symptom experienced by the patient was scored for the level of distress it caused on a 5-point (ie, 0 to 4) Likert scale (ie, ''not at all,'' ''a little bit,'' ''somewhat,'' ''quite a bit,'' and ''very much''). The burden of psychological symptoms was scored on a scale of 0 to 4 (corresponding to ''not at all,'' ''rarely,'' ''occasionally,'' ''frequently,'' and ''almost constantly'').…”
Section: Memorial Symptom Assessment Scale-short Form (Msas-sf)mentioning
confidence: 99%
“…61 A high prevalence of burdensome physical and psychological symptoms has been reported at all stages of HIV infection. 26,53,62,64,66 Pain is also experienced throughout the HIV disease trajectory, with severe pain experienced by 80 to 98% of those with advanced HIV. 4,43,57 Recent studies show that antiretroviral therapy (ART) has not eliminated the need for effective pain and symptom control, given that problems (sometimes treatment related) persist.…”
mentioning
confidence: 99%